2002
DOI: 10.1207/s15548430jlr3402_3
|View full text |Cite
|
Sign up to set email alerts
|

Effective Beginning Reading Instruction

Abstract: I argue that the National Reading Panel was too narrow in its presentation of scientifically-valid reading instructional research. Although the findings summarized by the Panel were valid, they were but a sampling of the many instructional practices that enjoy scientific support, most emphatically, in experiments and quasi-experiments (i.e., in the types of studies favored by the Panel). A sampler of practices that enjoy support but were ignored by the Panel is presented, as is discussion of qualitative resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0
13

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 72 publications
1
32
0
13
Order By: Relevance
“…Findings from multiple research studies have informed elements of effective early reading instruction (e.g., Allington & Johnston, 2002;Morrow, Tracey, Woo, & Pressley, 1999;Pressley, 2002;Pressley et al, 2001;Taylor, Pearson, Clark, & Walpole, 2000;Wharton-McDonald, Pressley, & Hampston, 1998). Among the most well-known syntheses of effective reading instruction is the National Reading Panel report (National Institute of Child Health and Human Development, 2000), which identified five key aspects of early readingphonemic awareness, phonics, fluency, text comprehension, and meaning vocabulary.…”
Section: Early Reading Intervention and Instructionmentioning
confidence: 99%
“…Findings from multiple research studies have informed elements of effective early reading instruction (e.g., Allington & Johnston, 2002;Morrow, Tracey, Woo, & Pressley, 1999;Pressley, 2002;Pressley et al, 2001;Taylor, Pearson, Clark, & Walpole, 2000;Wharton-McDonald, Pressley, & Hampston, 1998). Among the most well-known syntheses of effective reading instruction is the National Reading Panel report (National Institute of Child Health and Human Development, 2000), which identified five key aspects of early readingphonemic awareness, phonics, fluency, text comprehension, and meaning vocabulary.…”
Section: Early Reading Intervention and Instructionmentioning
confidence: 99%
“…Across a wide range of studies and reports, it has been concluded that parental involvement in early childhood through adolescent education generally benefits children's learning and school success, particularly in literacy (Chavkin, 1993;Durkin, 1966;Eccles & Harold, 1993;Epstein, 1989Epstein, , 1991Epstein, , 1994Postlethwaite & Ross, 1992;Pressley, 2002;Rasinski, 1989Rasinski, , 2003U.S. Department of Education, 1994).…”
mentioning
confidence: 99%
“…When reading instruction focuses on letter-, sound-, and word-level skills, lower-order literacy competencies are developed, but when reading instruction focuses on searching texts for information and making inferences, higher-order literacy competencies are developed that lead to the proficient comprehension of complex texts (Pressley, 2002). If greater emphasis is placed on lower-order literacy skill competencies during reading instruction, development of higher-order literacy skill competencies are compromised (Pressley, 2002).…”
Section: Reading Fluency Development In Young Learnersmentioning
confidence: 99%
“…When reading instruction focuses on letter-, sound-, and word-level skills, lower-order literacy competencies are developed, but when reading instruction focuses on searching texts for information and making inferences, higher-order literacy competencies are developed that lead to the proficient comprehension of complex texts (Pressley, 2002). If greater emphasis is placed on lower-order literacy skill competencies during reading instruction, development of higher-order literacy skill competencies are compromised (Pressley, 2002). While the compromise associated with an instructional focus on lower-order reading skills may lead to effective word recall, it often prevents readers from fully understanding the text they read, compromising development of higher-order reading skills (Pressley, 2002).…”
Section: Reading Fluency Development In Young Learnersmentioning
confidence: 99%
See 1 more Smart Citation